HUBUNGAN KARAKTERISTIK DEWAN KOMISARIS DAN PERUSAHAAN TERHADAP KEBERADAAN KOMITE MANAJEMEN RISIKO PADA PERUSAHAAN GO PUBLIC INDONESIA - Andarini, Putri; Januarti, Indira (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
This study aims to examine the association between board of commisioner and firm characteristics to the existence of risk management committee (RMC) and type of RMC, whether it is combined or separated from audit committee. The board of commisioner and firm characteristics used in this study are independent commisioner, board size, auditor reputation, complexity, financial reporting risk, leverage, and firm size. Population consists of Bursa Efek Indonesia (BEI)-listed companies from nonfinancial industry in 2007-2008. Sample was collected based on purposive sampling, and resulted 248 companies as a final sample. Data was collected from the annual report, and was analysed with logistic regression. The results, based on logistic regression analyses, indicated that firm size has a positive and significant association with the existence of RMC and separated RMC. The other variables (independent commisioner, board size, auditor reputation, complexity, financial reporting risk, leverage) have no significant association with the existence of RMC and separated RMC.